2006
DOI: 10.1093/annonc/mdj076
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of UCN-01 in combination with topotecan in patients with advanced solid cancers: a Princess Margaret Hospital Phase II Consortium study

Abstract: DLT was observed at DL 3 and RPTD was determined to be DL 2. To date, this combination has been relatively well tolerated with some preliminary evidence of efficacy. A phase II study of this combination in patients with ovarian cancer is underway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 22 publications
0
59
0
Order By: Relevance
“…This schedule, which appears to be well tolerated, results in free, salivary UCN-01 plasma concentrations of 800 to 1,400 nmol/L, which are sustained for up to 3 weeks following drug administration. Combination of the new UCN-01 schedule with topotecan or cisplatin has shown preliminary evidence of patient activity (46,47). In our animal studies, the theoretical peak UCN-01 concentration for treatment of mammary tumors with the drug, based on instantaneous absorption of the entire agent, would be in the range of f300 nmol/L.…”
Section: Discussionmentioning
confidence: 85%
“…This schedule, which appears to be well tolerated, results in free, salivary UCN-01 plasma concentrations of 800 to 1,400 nmol/L, which are sustained for up to 3 weeks following drug administration. Combination of the new UCN-01 schedule with topotecan or cisplatin has shown preliminary evidence of patient activity (46,47). In our animal studies, the theoretical peak UCN-01 concentration for treatment of mammary tumors with the drug, based on instantaneous absorption of the entire agent, would be in the range of f300 nmol/L.…”
Section: Discussionmentioning
confidence: 85%
“…Chk1 inhibition is being pursued as a promising target for the treatment of cancer (Blagden and de Bono, 2005). The oldest of such drugs, UCN-01, has been in development for the longest period of time and is now in Phase II clinical trials (Hotte et al, 2006). However, phase I trials revealed certain disadvantages of this drug, including dose-limiting toxicities (Kortmansky et al, 2005) and extremely long half-life due to binding to a1-acid glycoprotein (Fuse et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This therapeutic interest has led in recent years to the development of small molecules that selectively inhibit a particular component of the DNA damage response pathway, such as ATM, ATR, or the downstream cell cycle checkpoint kinases Chk1 and Chk2 (31). Chk1 has been of particular interest as a therapeutic target because its loss of function abrogates the G 2 cell cycle arrest and sensitizes even p53-deficient cancer cells to genotoxic agents, as best attested by studies with UCN-01, a known inhibitor that is currently in phase II clinical trials for patients with advanced cancers (14).…”
Section: Discussionmentioning
confidence: 99%
“…13) is a Chk1 inhibitor that abrogates the S-phase and G 2 -M checkpoints and potentiates the killing of cancer cells including those with p53 mutations by agents like cisplatin, camptothecin, and IR. Current phase II clinical trials in patients with advanced ovarian cancer, metastatic melanoma, large-cell lymphoma, and small-cell lung cancer will determine the clinical efficacy of UCN01 (14). The indocarbazole Go6976 is an effective inhibitor of Chk1 and Chk2 that abrogates the S and G 2 -M arrest and potentiates the cytotoxicity of a topoisomerase I inhibitor, but only in p53-defective cells (15).…”
Section: Introductionmentioning
confidence: 99%